2021
DOI: 10.1186/s12957-021-02360-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of latent biomarkers in connection with progression and prognosis in oral cancer by comprehensive bioinformatics analysis

Abstract: Background Oral cancer (OC) is a common and dangerous malignant tumor with a low survival rate. However, the micro level mechanism has not been explained in detail. Methods Gene and miRNA expression micro array data were extracted from the Gene Expression Omnibus (GEO) database. The differentially expressed genes (DEGs) and miRNAs (DE miRNAs) were identified by R software. Gene Ontology (GO) enrichment and Kyoto Encyclopedia of genes and genomes (K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…Recent studies suggested a pathogenic role of IL-17A in cancer. For example, the IL17 and PI3K-Akt signaling pathway are enriched in oral cancer [ 25 ]. The canonical IL-23/IL-17A pathway is activated in the tracheal mucosa of idiopathic subglottic stenosis patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested a pathogenic role of IL-17A in cancer. For example, the IL17 and PI3K-Akt signaling pathway are enriched in oral cancer [ 25 ]. The canonical IL-23/IL-17A pathway is activated in the tracheal mucosa of idiopathic subglottic stenosis patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have stated that PI3K/AKT can be a pro-in ammation effector in oral diseases like periodontitis [44]. They can also affect the process of different kinds of oral squamous cancers [45]. However, in pulpitis and dental pulp speci c cells like the odontoblasts, their relationship still needs experimental evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Given their diverse cell biological roles, DExD/H box RNA helicases are associated with the development of many diseases such as cancer, aging, neurologic and immunologic disorders, and infectious disease (Steimer & Klostermeier, 2012). DDX60 expression has been shown to be dysregulated and associated with advanced disease and response to treatment of different cancers, such as oral cancers (Fu et al, 2016; Reyimu et al, 2021), gliomas (Zhang et al, 2021), and breast cancers (Ríos-Romero et al, 2020; Xin et al, 2020). Additionally, DNA methylation variability in DDX60 is associated with cases of mixed connective tissue disease (Carnero-Montoro et al, 2019).…”
Section: Discussionmentioning
confidence: 99%